Tinjauan Yuridis Akibat Hukum dari Pecahnya Wadah Tunggal Organisasi Advokat dalam Sistem Peradilan Pidana di Indonesia - Anna Astuti; Eko Nurharyanto (Kajian Hasil Penelitian Hukum, 2019)
This study aims to examine and analyze the factors underlying the breakup of the single forum of advocate organizations in the criminal justice system in Indonesia and the legal consequences of the breakup of a single forum of advocate organizations in the criminal justice system in Indonesia.This type of research is empirical juridical. The data used in this study are primary data and secondary data. Data collection is done by document study and interviews. Data analysis in this study used qualitative analysis.Based on the results of the study, it was concluded that, the things behind the break-up of a single forum of advocate organizations in the criminal justice system in Indonesia, the government slowly passed lawyers' advocates, the role of the government that was inconsistent in implementing law advocates, and the Supreme Court's interference in organizational issues advocate.The legal consequences of the breaking up of a single forum of advocate organizations in the criminal justice system in Indonesia will not have an impact on the justice system but have an impact on justice seekers. This is because Advocates in carrying out their duties aim at upholding law, truth and justice. Thus, the provision of legal assistance to perpetrators of criminal acts is a form of service of Advocates in carrying out their profession as one of the elements of law enforcement officers, not depending on whether advocates are members of advocate organizations or not, as stipulated in Government Regulation Number 38 of 2008 concerning Requirements and Procedures for Granting Legal Aid.